2013
DOI: 10.5194/acp-13-6049-2013
|View full text |Cite
|
Sign up to set email alerts
|

Observation of horizontal winds in the middle-atmosphere between 30° S and 55° N during the northern winter 2009–2010

Abstract: Abstract. Although the links between stratospheric dynamics, climate and weather have been demonstrated, direct observations of stratospheric winds are lacking, in particular at altitudes above 30 km. We report observations of winds between 8 and 0.01 hPa (~35–80 km) from October 2009 to April 2010 by the Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES) on the International Space Station. The altitude range covers the region between 35–60 km where previous space-borne wind instruments show a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 60 publications
1
46
0
Order By: Relevance
“…For this purpose, realistic background winds are required for the period and altitude range considered. Previous studies have shown that zonal winds in the tropics provided by ECMWF are in good agreement with observations (e.g., Baldwin and Gray, 2005;Dee et al, 2011;Baron et al, 2013). In particular, there is qualitatively good agreement between the QBO-related gravity wave drag variations derived from the ECMWF ERAInterim reanalysis and those derived from satellite observations .…”
Section: Era-interim and The Tem Zonal Momentum Budgetsupporting
confidence: 69%
See 1 more Smart Citation
“…For this purpose, realistic background winds are required for the period and altitude range considered. Previous studies have shown that zonal winds in the tropics provided by ECMWF are in good agreement with observations (e.g., Baldwin and Gray, 2005;Dee et al, 2011;Baron et al, 2013). In particular, there is qualitatively good agreement between the QBO-related gravity wave drag variations derived from the ECMWF ERAInterim reanalysis and those derived from satellite observations .…”
Section: Era-interim and The Tem Zonal Momentum Budgetsupporting
confidence: 69%
“…Even though fewer and fewer data are assimilated in ERAInterim at increasing altitude, the SAO zonal winds should be quite reliable (e.g., Baldwin and Gray, 2005;Dee et al, 2011;Baron et al, 2013). Consequently, the zonal wind tendency ∂u/∂t, which is determined directly from u, should also be quite reliable.…”
Section: Ern Et Al: Gravity Wave Driving Of the Saomentioning
confidence: 99%
“…Satellite measurements of mesospheric winds down to 80 km were determined from Aura Microwave Limb Sounder (MLS) observations of Doppler-shifted, Zeeman-split O 2 σ − and σ + lines around 118.75 GHz . Winds at 35-80 km were observed for a limited time over the latitude range 30 • S to 55 • N using ozone (O 3 ) and hydrogen chloride emission line measurements in the 625-650 GHz range by the Submillimeter-Wave Limb-Emission Sounder (SMILES) (Baron et al, 2013). The Atmospheric Laser Doppler Instrument (ALADIN) on the forthcoming Atmospheric Dynamics Mission (ADM) Aeolus satellite will make UV lidar measurements of winds in the troposphere and lower stratosphere (Stoffelen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, a cross comparison with the retrievals from other lines should help us to significantly reduce this bias. The bias that does not change for a long time can also be mitigated by using the fact that the equatorial flow is predominantly zonal at these altitudes (Baron et al 2013a) or comparing the retrievals with mid-latitude winds from meteorological analyses and reanalyses.…”
Section: Wind Retrievalsmentioning
confidence: 99%
“…Unlike the shorter wavelengths, SMM lines are not affected by nonlocal thermodynamic equilibrium. Also, their large potential for global wind measurements in the stratosphere, mesosphere, and lower thermosphere has been demonstrated using the Doppler shifts of the 118.75 GHz O 2 line measured by the Microwave Limb Sounder (MLS) ) and the O 3 and HCl lines near 625 GHz measured by the Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES) (Baron et al 2013a). …”
Section: Introductionmentioning
confidence: 99%